Características seminais e resfriamento de sêmen de tamanduá (Myrmecophaga tridactyla) de vida livre - Luba, Camila do Nascimento [UNESP] (2014)
The giant anteater (Myrmecophaga tridactyla) is considered vulnerable to extinction and scientific data regarding andrology and seminal characteristics are scarce. The semen were collected from eight animals with the intention of seminal parameters to establish anteaters free life as regards the volume, odor, color, motility, vigor, concentration and morphology, and to investigate the time the semen remains with motility and vigor under refrigeration at a temperature of 5 ° C. The sperm motility and vigor were subjectively assessed by light microscopy and morphological analysis of sperm were performed by conventional optical microscopy, differential interference contrast microscopy and transmission electron microscopy. The ejaculate was characterized with two distinct fractions (fraction whitish, milky and rich in sperm cells, and gel fraction colorless and viscous with absence of sperm) and average volume 0.75 ml (± 0.13). The mean values of the parameters (± standard error) found in the fresh semen samples motility were 75% (± 2.98), vigor 3.21 (± 0.29), concentration x106/ml 108.5 (± 13.46), index of plasma membrane integrity of 71% (± 4.01) and sperm abnormalities in karras-modified staining 35.5% (± 3.38) and 48.37% (± 6.83) in contrast microscopy differential interference. When subjected to cooled semen presented motility and vigor up to 24 hours, with decreasing values in both parameters over time